Achievement of Maternal Mortality Ratio (MMR) below the National Level in Jharkhand - Kumar, Abhishek; Shikha, Swati; Begum, Jarina; Ali, Syed Irfan (Indian Journal of Community Health, 2023)
An indicator of the reproductive health of women in an area is the maternal mortality rate. A lot of women in the reproductive age range pass away from difficulties during, during, or related to pregnancy, childbirth, or abortion. No matter the length or location of the pregnancy, the World Health Organization defines maternal death as "the death of a woman while pregnant or within 42 days of termination of pregnancy, from any cause related to or aggravated by the pregnancy or its management but not from accidental or incidental causes".(1)